Fotodegradação no UV-C e fotoestabilização em polímeros utilizados na indústria médico-hospitalar - Gimenez, Jessica Caroline Ferreira (Universidade Federal de São Carlos, 2025)
The cross-contamination concerns that came to light during the SARS-CoV-2 pandemic in 2019 emerged the use of UV-C germicidal lamps. However, despite its proven efficiency against pathogens, UV-C light promotes damage in materials such as polymers. While there is extensive literature on polymer photodegradation under UV-A and UV-B, studies on UV-C remain scarce. This gap formed the basis of the present work, which aims to provide a comprehensive understanding of UV-C effects on polypropylene (PP), a commodity polymer used in syringes, and poly(ether sulfone) (PESU), a high-performance polymer used in medical structural equipment, as well as to evaluate strategies for their photostabilization. Our findings reveal that PP became unstable during rheological measurements, displaying an unusual increase in the complex viscosity. 1H Time Domain NMR indicated that UV-C favors branching reactions over crosslinking. A Design of Experiment was employed to determine optimal PP photostabilization when combining titanium dioxide (TiO2) with few-layer graphene (FLG) or Irganox B215 (B215). Electron Paramagnetic Resonance showed that incorporating radical scavengers with TiO2 reduced hydroxyl formation by ~30% for the FLG mixture and ~25% for the B215 mixture. The study also compared continuous and cyclic UV-C exposure modes in PESU. Tensile tests demonstrated that even 1 hour of UV-C exposure significantly reduced PESU’s mechanical performance. Infrared, XPS, and rheological analysis revealed more pronounced changes in samples under cyclic exposure. Finally, PESU/FLG and PESU/graphene oxide (GO) were exposed under UV-C irradiation. Infrared results showed that FLG mitigated hydroxyl formation, while GO composites had a minimal effect. Tensile tests revealed that UV-C considerably increased the Young’s Modulus. This work provides remarkable findings into UV-C photodegradation and photostabilization of PP and PESU, highlighting subtle differences in the degradation mechanisms induced by UV-C and presenting strategies for photoprotection.

La préoccupation concernant la contamination croisée, apparue lors de la pandémie de SARS-CoV-2 en 2019, a mis en évidence l’utilisation de lampes germicides UV-C. Cependant, malgré leur efficacité avérée contre les agents pathogènes, la lumière UV-C provoque des dommages aux matériaux tels que les polymères. Bien qu’il existe une vaste littérature sur la photodégradation des polymères sous UV-A et UV-B, les études en UV-C demeurent rares. Cette lacune a motivé le présent travail, qui vise à comprendre les effets du rayonnement UV-C sur le polypropylène (PP), utilisé dans les seringues, et sur la poly(éther sulfone) (PESU), appliquée dans des composants médicaux, ainsi qu’à évaluer des stratégies de photoprotection. Les résultats ont montré que le PP présentait une augmentation inhabituelle de la viscosité complexe lors des essais rhéologiques, et la RMN du domaine temporel de l’hydrogène (¹H) a indiqué que l’UV-C favorise les réactions de ramification. Un plan d’expériences (DoE) a été employé pour optimiser la photoprotection du PP en combinant le dioxyde de titane avec du graphène à quelques couches (FLG) ou l’Irganox B215 (B215). La résonance paramagnétique électronique a révélé que l’ajout de FLG réduisait jusqu’à 30 % la formation d’hydroxyles, tandis que B215 réduisait de 25 %. L’étude a comparé les modes d’exposition continue et cyclique aux UV-C sur le PESU. Des essais de traction ont montré qu’une heure d’exposition réduisait déjà significativement les performances mécaniques. Analyses infrarouges, XPS et rhéologiques ont confirmé des altérations plus prononcées sous exposition cyclique. Enfin, des composites PESU/FLG et PESU/oxyde de graphène (GO) ont été évalués. Le FLG atténuait la formation d’hydroxyles, tandis que les composites avec GO présentaient un effet minimal, et les essais mécaniques ont montré une augmentation du module de Young. Ce travail fournit des résultats pertinents sur la photodégradation et la photoprotection du PP et du PESU sous UV-C, mettant en évidence les différences subtiles dans les mécanismes de dégradation et proposant des stratégies de photoprotection.
UV-C photodegradation and stabilization of polymers used in the medical-hospital industry
Keywords: UV-C; Fotodegradação; Fotoproteção; Grafeno; PP; PESU; Photodégradation; Photostabilisation; Graphène; Photodegradation; Photostabilization; Graphene; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; CIENCIAS EXATAS E DA TERRA::QUIMICA; 9. Indústria, Inovação e Infraestrutura